"Inferiority" Complex? Policing, Private Precautions and Crime - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2015)
I link the idea that greater state policing induces private neglect of safety precautions (moral hazard) with the concept of “inferior inputs” in the production function literature. I model crime prevention as an outcome of two “inputs”—policing (a public good) and private security expenses. I show that if cost-minimizing individuals choose insufficient private expenses to completely deter crimes, a rise in policing raises criminals’ probability of success if and only if policing is an “inferior input” in crime prevention. This is so even though the marginal productivity of policing is always positive, and works through a strong moral hazard effect. I discuss implications for policy-makers.